Physical Rehabilitation Core Outcomes In Critical illness (PRACTICE): protocol for development of a core outcome set - Connolly, Bronwen (Trials, 2018)
BACKGROUND: Existing data on physical rehabilitation interventions in critical illness are challenged by outcome heterogeneity that limits data synthesis and translation of research findings into clinical practice. This protocol describes the PRACTICE study to develop a core outcome set (COS) for trials of physical rehabilitation interventions delivered across the continuum of a patient’s recovery from the intensive care unit until reintegration in the community following hospital discharge. METHODS: Mixed methods will be used including: systematic reviews of quantitative and qualitative literature; qualitative interviews with patients and caregivers; a modified Delphi consensus process with researcher, clinician and patient/caregiver stakeholder groups; and consensus meetings for ratification of findings, resolving uncertainty, or developing an action plan for COS implementation. DISCUSSION: The PRACTICE COS will inform relevant stakeholders about important outcomes regarding physical rehabilitation in critical illness, and may enhance the future design and conduct of trials in this area. TRIAL REGISTRATION: COMET database (www.comet-initiative.org/, Record ID 288, 01/03/13). PROSPERO database (CRD42014008908, CRD42017078549). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2678-4) contains supplementary material, which is available to authorized users.